PERFORMANCE SUPERVISI KEPALA SEKOLAH DALAM MENGEMBANGKAN ETOS KERJA GURU - Meylani Witaningrum; Abdul Halik; Muhammad Alwi; Hasmiah Herawaty; Anwar Anwar (Jurnal Manajemen Pendidikan, 2026)
This study aims to (1) determine the work ethic of teachers at SDN 62 Parepare, (2) determine the performance of the principal's supervision in developing the work ethic of teachers at SDN 62 Parepare.  The type of research used is qualitative research with a case study approach, which involves observation, interview, and documentation techniques. The collected data were then analyzed using a qualitative descriptive method, which includes data reduction, data display (data presentation), as well as drawing conclusions and verification.  The results of the study indicate the following: (1) The work ethic of teachers at SDN 62 Parepare is reflected in their high commitment to students and colleagues. The teachers demonstrate consistent dedication in carrying out their duties. Through the Learning Community (KOMBEL), teachers collaborate effectively and utilize good communication with fellow teachers and students to improve teaching strategies and build an inclusive learning environment. However, there are challenges such as sometimes there are limitations in resources such as time, funds, and facilities, as well as the need to improve understanding of individual student needs. Teachers also often have difficulty identifying weaknesses and strengths in their professional development. (2) The principal is actively involved in the planning, implementation, and follow-up of supervision results by holding structured meetings or gatherings with teachers